Metabolic dysfunction-associated fatty liver disease is an early predictor for testosterone deficiency in aging men without metabolic syndrome - Liu, Chia-Chu; Huang, Shu-Pin; Lee, Yung-Chin; Lee, Cheng-Hsueh; Huang, Tsung-Yi; Geng, Jiun-Hung; Chang, Che-Wei; Lin, Chung-Yu; Juan, Yung-Shun; Wu, Wen-Jeng; Hsieh, Tusty-Jiuan (Frontiers in Endocrinology, 2023)
Background and aims: Metabolic dysfunction-associated fatty liver disease (MAFLD) has emerged as a valuable marker for identifying individuals at increased risk of metabolic dysfunction, liver-related complications, and cardiovascular disease.However, the association between MAFLD and testosterone deficiency (TD) in aging men remains poorly understood. This study aimed to investigate the association between MAFLD and the risk of TD in aging Taiwanese men, with a specific focus on those without metabolic syndrome (MetS).Methods: A free health screening program was conducted for Taiwanese men aged over 40 years in Kaohsiung, Taiwan. Participants underwent physical examinations, completed questionnaires regarding demographics, medical history, and clinical symptoms of TD, and provided 20-mL whole blood samples for biochemical, adipocytokine, and hormonal evaluations. Fatty liver index was used to evaluate the risk of fatty liver. Diagnostic criteria for MAFLD included fatty liver along with overweight/obesity, type 2 diabetes, or evidence of metabolic dysregulation.Results: A total of 631 men (mean age: 54.4 ± 8.4 years) were enrolled. The prevalence rates of TD and MetS were significantly higher in men with MAFLD compared to those without (both p < 0.001). Additionally, the presence of MAFLD showed a significant correlation with adipocytokines associated with insulin resistance, such as adiponectin, leptin, and retinol-binding protein-4 (RBP-4) levels (all p < 0.001). Among men without MetS, those with MAFLD had a 3.89-and 4.74-fold higher risk of total testosterone < 300 ng/dL and TD, respectively, after adjusting for potential covariates.MAFLD is associated with an elevated risk of TD in aging Taiwanese men, particularly in the absence of MetS. This finding suggests that MAFLD could serve as an early predictor of TD, facilitating the identification of high-risk individuals and enabling timely interventions. Further research is needed to validate these findings and explore the underlying mechanisms linking MAFLD, TD, and MetS in diverse populations.